2012
DOI: 10.1080/00222895.2012.681321
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Motion Analysis and Muscle Activation Patterns of Continuous Reaching in Survivors of Stroke

Abstract: Coordinated reaching requires continuous interaction between the efferent motor output and afferent feedback; this interaction may be significantly compromised following a stroke. The authors sought to characterize how survivors of stroke generate continuous, goal-directed reaching. Sixteen survivors of stroke completed functional testing of the stroke-affected side and a continuous reaching task between 2 targets with both sides. Motion analysis and electromyography data were collected to determine segmental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Numerous studies have demonstrated that stroke patients exhibit excessive trunk movements during pointing and reaching, [6][7][8][9][10][11][12][13] a compensatory motor strategy to extend arm reach when shoulder and elbow movement and control is impaired. 14,15 Excessive use of compensatory movements can result in secondary complications such as muscle contractures, joint misalignment, pain, limb disuse, and increased energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that stroke patients exhibit excessive trunk movements during pointing and reaching, [6][7][8][9][10][11][12][13] a compensatory motor strategy to extend arm reach when shoulder and elbow movement and control is impaired. 14,15 Excessive use of compensatory movements can result in secondary complications such as muscle contractures, joint misalignment, pain, limb disuse, and increased energy expenditure.…”
Section: Introductionmentioning
confidence: 99%
“…13 Subjects were seated in a 45cm chair with no arm rests, and their hands flat (about shoulder width apart) on a 70cm table in front of them. Their chest was restrained by a Velcro strap to limit compensatory trunk movements, 16,17 and their humerus was hanging down their body. Each subject performed 5 repetitions of two reaching tasks with the paretic and non-paretic UE.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, loss of some functional abilities can be observed; among them is reaching [11]. The ability to achieve adequate reach is a fundamental component of daily activities [12] and, considering that this task requires precise planning [13,14], damage to the central nervous system can result in reduced capacity to activate and modulate the muscles involved in its execution [8]. Therefore, the individual will often compensate [15] in the execution of motor tasks, e.g.…”
Section: Introductionmentioning
confidence: 99%